The influence of social context on food-evoked emotion : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Psychology at Massey University, Albany, New Zealand - Nath, Elizabeth (Massey University, 2021)
Emotion measurement has seen exponential growth in recent years as consumer and sensory scientists realise that our emotional responses to food are better at predicting choice and purchase behaviour compared to hedonic or sensory evaluations alone. However, despite a large body of evidence pointing to the context-dependent nature of emotion, insufficient attention has been placed on quantifying the impact of contextual variables on consumption emotion. In this thesis, I first investigate the effects of timing, location and social setting on explicit emotional responses using a survey methodology. It was found that social meals amplified positive emotion relative to solitary meals, and that sociality and location had a larger effect on self-reported emotion compared to meal timing. I then focus on social context effects on implicit emotion using facial electromyography as a measure of the expressive component of emotion. In two closely related experiments, participants’ facial affective responses were recorded as they viewed and rated food images in the presence of a researcher, a friend, or a stranger. Analyses revealed that facial muscle activity indicative of a disgust response was inhibited in the presence of a researcher but amplified in the presence of a co-acting stranger. These findings are discussed with reference to Basic Emotions Theory and the Behavioural Ecology View of facial expressions. Finally, in exploratory analyses, I consider temporal patterns of facial responding and discuss their relationships with social context and subjective preference. The findings presented in this thesis may hopefully serve as a springboard for further investigations into contextual influences on food-evoked emotion.
Keywords: Food habits; Social aspects; Psychological aspects; Emotions; 520406 Sensory processes, perception and performance